Deviation in the Poetry of Mushfiq Kāshānī - Mrayam Khalili Jahantigh; Tara Mohammadi (مطالعات زبانی و بلاغی)
Deviation in art refers to going beyond the conventional language in order to evoke a sense of pleasure, perception, and understanding in the recipient. It can be classified as semantic deviation (which explores metaphor, metonymy, irony and synesthesia) and combinative deviation (which examines the textual elements such as vocabulary, syntax, phonetics, writing style, and dialect). This artistic technique is found in both prose and poetry, aiming to captivate the audience through highlighting certain aspects. Poetic deviation is evident in the poetry of Abbās Keymanish, known as Mushfiq Kāshānī, a contemporary religious and revolutionary poet. As such, this research employs a descriptive-analytical approach to investigate the components of deviance in his poetry and explore his poetic deviations. In so doing, the study examines linguistic, semantic, syntactic, archaic, and stylistic elements of deviation according to Geoffrey Leech's theory. The findings reveal that Mushfiq Kāshānī's poetry can be considered a comprehensive reflection of artistic beauty and innovation, with the most frequent component of deviation occurring in the realm of meaning. The audience understand the poet's intended meaning beneath these aesthetic qualities, linguistic and syntactic deviations, and other components that are less frequent in his poetry.